P0S7-KALIGRAFI: TEROBOSAN SENI KALIGRAFI (ARAB) DI TENGAII PERKEMBANGAN SENI KONTEMPORER DI INDONESIA - Vfikke Susanto (Ars: Jurnal Seni Rupa dan Desain, 2008)
Postmodernism has indeed provided a priceless contribution in how the world o f Arabic calligraphy isenjoyed. This article is attempting to re-examine calligraphy by observing the various styles in Indonesia.By doing this. Arabic calligraphy itt Indonesia which was considered a dying art can hopefully be rebuilt.An important concluding note is the reawakening o f the attitude to discover local ability, including how todevelop a stance towards the internationalisation o f art.Keywords: locality, post-calligraphy, postmodernism